Reseña de Ortiz, Renato (2014) Universalismo/Diversidad. Contradicciones de la modernidad-mundo, Prometeo, Buenos Aires, 174 páginas. - Cárcamo, Magdalena (2015)
Fil: Fil: Cárcamo, Magdalena. Universidad Nacional de Rosario; Argentina.